2023
DOI: 10.1021/acsmaterialslett.2c00991
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed High-Frequency Dielectric Elastomer Actuator toward Insect-Scale Ultrafast Soft Robot

Abstract: Insects with small and light bodies possess the capability of agile and fast movement in a small space. Inspired by nature, an insect-like soft robot may update the strategies in many scenarios like exploration, rescue, etc. However, the design and mass manufacture of soft robots combining insect size, fast mobility, good robustness, and impact-perception capability still present great engineering challenges. Herein, we report an insect-scale (15 mm body length (BL), 450 mg body weight) and ultrafast (∼4.0 BL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…With the gradual increase of interdisciplinary convergence and technological convergence, many new areas of development have emerged, such as implantable medical devices, soft robots, wearable devices, electronic fabrics, etc. Particularly, the rise of personalized healthcare has spurred the development of flexible wearable and implantable electronic devices for monitoring physiological signals. Compared to conventional 3D and 2D electronic devices, fiber-based electronic devices have the advantages of high aspect ratio, lightweight, high flexibility, and weavability. When applied to the skin, it can achieve a high degree of adaptability to the skin, thereby improving the comfort of the human body and enhancing signal fidelity during motion. , In health monitoring, fiber-based flexible sensors can monitor large-scale (such as the fingers, arms, and legs) and small-scale (such as emotional expression of face, breathing, and swallowing) human body movements to diagnose vocal cord damage, respiratory disorders, angina pectoris, etc. , Typically, the reported fiber-based sensors use stretchable elastomers, such as polydimethylsiloxane (PDMS), Ecoflex, and polyurethane (PU), as substrates with the conductive materials coated on the surface or embedded in the matrix to realize a close fit with the human body. For instance, Seyedin et al prepared a fiber-based wearable strain sensor with Ti 3 C 2 T x MXene embedded in PU by wet spinning, which exhibited high sensitivity and could be used to monitor elbow joint movement.…”
Section: Resultsmentioning
confidence: 99%
“…With the gradual increase of interdisciplinary convergence and technological convergence, many new areas of development have emerged, such as implantable medical devices, soft robots, wearable devices, electronic fabrics, etc. Particularly, the rise of personalized healthcare has spurred the development of flexible wearable and implantable electronic devices for monitoring physiological signals. Compared to conventional 3D and 2D electronic devices, fiber-based electronic devices have the advantages of high aspect ratio, lightweight, high flexibility, and weavability. When applied to the skin, it can achieve a high degree of adaptability to the skin, thereby improving the comfort of the human body and enhancing signal fidelity during motion. , In health monitoring, fiber-based flexible sensors can monitor large-scale (such as the fingers, arms, and legs) and small-scale (such as emotional expression of face, breathing, and swallowing) human body movements to diagnose vocal cord damage, respiratory disorders, angina pectoris, etc. , Typically, the reported fiber-based sensors use stretchable elastomers, such as polydimethylsiloxane (PDMS), Ecoflex, and polyurethane (PU), as substrates with the conductive materials coated on the surface or embedded in the matrix to realize a close fit with the human body. For instance, Seyedin et al prepared a fiber-based wearable strain sensor with Ti 3 C 2 T x MXene embedded in PU by wet spinning, which exhibited high sensitivity and could be used to monitor elbow joint movement.…”
Section: Resultsmentioning
confidence: 99%
“…The high‐frequency oscillation characteristics of DEA, especially the resonance, provide a solution for the rapid movement of mobile robots. [ 170 ]…”
Section: Applicationsmentioning
confidence: 99%
“…The high-frequency oscillation characteristics of DEA, especially the resonance, provide a solution for the rapid movement of mobile robots. [170] The minimum energy structure is widely adopted in designing mobile robots driven by acrylic-based DEAs. Gu et al [171] reported a soft wall-climbing peristaltic robot with a DEA body and two electroadhesive feet as shown in Figure 7a.…”
Section: Mobile Robotsmentioning
confidence: 99%
“…Soft robotics has emerged as a rapidly evolving field, offering environmental adaptation and autonomy for navigating challenging terrains and environments. [ 1 , 2 , 3 , 4 ] Compared with the conventional robots using rigid components, soft robots that utilize soft actuators are highly environmentally adaptive and deformable into different shapes for various environments and can be effectively miniaturized to the centimeter scale or smaller. [ 5 , 6 , 7 ] In particular, they can find uses in complex, enclosed, or narrow spaces, such as gaps and vessels, and can navigate in maze‐like spaces.…”
Section: Introductionmentioning
confidence: 99%